MEASURING FINANCIAL PERFORMANCE THROUGH MANAGERIAL CAPABILITIES AND STRATEGIC INNOVATION IN THE ERA OF DIGITAL TECHNOLOGY - Heni Pujiastuti (Faculty of Economic and Business Universitas STIKUBANK, 2023)
The stretching of Indonesia's economic growth after Covid 19 shows conditions that are increasing, this can be seen from the business activities that have started to be carried out for people in villages and urban areas. This opportunity for the people of Rejoso village, Nganjuk Regency, is an opportunity that is very exploited so that traded products are able to penetrate big cities in East Java. The purpose of this study is to analyze the ability of businesses to create financial performance and to analyze the factors that influence the achievement of financial performance. This type of research is a quantitative research using primary data for the July 2022 period and distributing questionnaires to 110 MSMEs. The data source is from the Nganjuk Regency Cooperative and MSME Office. The analysis of this study uses the financial performance index and SEM PLS. The results show that managerial ability and innovation in achieving good financial performance have been achieved with an index of 96.91. These results are in line with the test results where the statistical T values ​​and P values ​​are in areas that are significant.